Drogas e redes sociais de suporte: uma possibilidade de cuidado - Bortolai, Letícia Andriolli (Universidade Federal de São Carlos, 2020)
The “problem of drugs” has been understood as a complex phenomenon involving different aspects, especially the social situation. One of the strategies that has been debated is the understanding of the issues involving drugs in reference to social support networks. This knowledge is important for improving care for who uses drug in a prejudicial way related to health and social services. The social support networks are the dimensions that compose the social integration of someone, with emphasis on work relationships and sociability, primary and secondary, including social services. Based on this perspective, the objective of this study is to investigate, from the point of view of who uses drugs, how social support networks are organized and structured and what are the main elements that constitute them. Making use of the theoretical-methodological from the social occupational therapy, as well as the social understanding about drugs, a study was conducted in a Psychosocial Care Center - Alcohol and other Drugs (CAPS ad) for the period of six months. The study was conducted on the basis of observation, interviews and group activities, associated with the field diary containing all the data collected. It was identified that the social support networks from people who use drugs are composed of different elements. The informal dimension is made up of family, church, and work, including the relationships established in each location. In the formal context, the emphasis was social institutions, primarily to CAPS ad. However, for the most part, few supports are presented to contribute to an effective inclusion and participation in their social life, besides the lack of successful social policies. The consequences are people who use drugs in the path of marginalization and receiving insufficient social supports, including from public services that should guarantee the mediation to their rights. It was verified that it is necessary to have social services that offers different support for people who use drugs, expanding their social networks; helping them to have lasting relationships; considering their subjectivities and different care demands; supporting on the mediation by health professionals. In conclusion, the purpose of this study is to defend occupational therapy as a professional with abilities to contribute to the care process.
Drugs and social support networks: a possibility of care
Keywords: Terapia ocupacional social; Prática profissional; Políticas sociais; Redes de apoio; Social occupational therapy; Professional practice; Social policies; Support networks; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL